Determination of economic injury level for pod borers of chickpea in dry farms of Ilam province - A. Jozeyan; Gh. R. Rajabi; B. Gharali (نامه انجمن حشره‌شناسی ایران, 2007)
Chickpea, one of the major pulses, is planted together with wheat as a custom rotation in Ilam province. Pod borers are serious pest of chickpea and their direct damage to seed reduce yield considerably. Annually, farmers use much pesticide against the pest without any clue. In order to determine economic injury level (EIL), a semi-field study was started in 2000 to calculate this parameter based on a complete randomized block design with five treatments and four replications. Emerged larvae in the surrounding chickpea fields were collected and released in cages at the density of 0, 10, 20, 40, 80 larvae per square meter. Various factors (e. g. yield, damaged and total seeds) were measured and analyzed at harvesting time. Results show that if market value of chickpea and cost of management (treatment) are considered 3500 rials per kg and 150000 rials, respectively, then EIL will be 3.9 larvae per square meter (four rows with a length of one meter).